Cytochrome P450 Omega-Hydroxylase 4a14 Attenuates Cholestatic Liver Fibrosis - Li, Sha; Wang, Chenghai; Zhang, Xiaxia; Su, Wen (Frontiers in Physiology, 2021)
Background Cholestasis is a pathological condition involving obstruction of bile secretion and excretion that results in hepatotoxicity, inflammation, fibrosis, cirrhosis, and eventually liver failure. Common bile duct ligation (BDL) model is a well-established murine model to mimic cholestatic liver fibrosis. We previously reported that cytochrome P450 omega-hydroxylase 4a14 (Cyp4a14) plays an important role in the pathogenesis of non-alcoholic fatty liver disease (NAFLD)-related fibrosis. The goal of this study was to determine the role of Cyp4a14 in cholestatic-induced liver fibrosis. Methods C57BL/6 mice were subjected to BDL for 14 days, and Cyp4a14 mRNA and protein levels were examined and compared with those of the sham group. Cyp4a14 knockout mice and adeno-associated virus (AAV)-mediated overexpression of Cyp4a14 in C57BL/6 mice underwent BDL and liver histology, and key fibrosis markers were examined. Results Both hepatic Cyp4a14 mRNA and protein levels were markedly reduced in BDL liver compared with the time-matched sham group. Cyp4a14 gene-deficient mice aggravates whereas its overexpression alleviates BDL-induced hepatic fibrosis, which were determined by liver function, liver histology, and levels of key fibrotic markers including α-smooth muscle actin (α-SMA), transforming growth factor-β1 (TGF-β1), and collagen 1a2 (Col1a2). Conclusion Cyp4a14 exerts a contrasting role in different hepatic fibrosis models. Strategies that enhance Cyp4a14 activity may be potential strategies to cholestatic related liver fibrosis.